Anxiolytic-like Effect Characterization of Essential Oil from Local Lavender Cultivation - Sol Micaela Angulo; Victoria Belén Occhieppo; Cristian Moya; Rosana Crespo; Claudia Bregonzio (Pharmaceuticals)
Background: Anxiety disorders have a 7.3% worldwide prevalence and, considering the long period of treatment, developing new efficient and safer pharmacological tools is critical. Essential oils consist of highly concentrated lipophilic compounds from plants with therapeutic potential effects, such as Lavandula burnatii, produced in Córdoba, Argentine, with high levels of active pharmaceutical ingredients in its essential oil (linalyl acetate and linalool). The evidence indicates that lavender essential oil could induce anxiolytic effects; however, more systematic studies are needed. Methods: To test the anxiolytic attributes of Lavandula burnatii, male Wistar rats (200–260 g) were injected intraperitoneally with two different doses of essential oil (30/80 mg/kg) or vehicle (Myritol 318, a high-purity vegetable oil), once (acute) or for 7 days. One hour after the last administration, the anxiolytic effects were evaluated using the following behavioral tests: the dark–light test and the elevated plus maze test. The open-field test was used to assess locomotor activity. Results: Our results showed that the lower dose of lavender essential oil induces anxiolytic effects since it increases the time spent in the aversive compartment in each evaluation. The acute administration has no impact on the behaviors evaluated. The higher dose is comparable with the control group and does not show significant differences. Conclusions: More studies are needed to better characterize the beneficial effects of this essential oil for anxiety disorders and to establish an adequate dosage range.